2016
DOI: 10.14687/jhs.v13i2.3752
|View full text |Cite
|
Sign up to set email alerts
|

Compassion fatigue: A Study of critical care nurses in Turkey

Abstract: This study was conducted to determine the level of compassion fatigue which experienced by nurses who work in intensive care units and factors that affecting it.In a cross sectional design, critical nurses were surveyed by using questionnaire and  compassion fatigue (CF) subscale of the Professional Quality of Life Scale (ProQOL R-IV) to measure levels of compassion fatigueat a large National Education and ResearchHospital located in northwestof Turkey. A total of 69 critical care nurses participated in the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 13 publications
(18 reference statements)
4
16
0
Order By: Relevance
“…The increasing length of experience resulted in a lower risk of compassion fatigue. These findings parallel previous studies [6, 12, 25, 38]. Another related finding suggests that novice and advanced beginner nurses are more likely to experience lower levels of CS and a higher risk of BO than competent, proficient, and expert nurses.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The increasing length of experience resulted in a lower risk of compassion fatigue. These findings parallel previous studies [6, 12, 25, 38]. Another related finding suggests that novice and advanced beginner nurses are more likely to experience lower levels of CS and a higher risk of BO than competent, proficient, and expert nurses.…”
Section: Discussionsupporting
confidence: 89%
“…In this study, nurses with a higher level of education (post-BSN education) were most likely to experience compassion fatigue compared with nurses holding an Associate Degree, Diploma, and BSN, while Dikman et al [12] reported that nurses with Associate Degrees had a higher risk of compassion fatigue than other educated groups. Wu et al [6] also reported that more educated nurses were found to experience higher levels of CS.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Compassion fatigue is the emotional, biological, and physiological exhaustion due to being continuously exposed to others' suffering for a long time and is characterized by the gradual decrease in compassion over time. Healthcare professionals constitute a high-risk group in terms of compassion fatigue 22 . Midwifery plays a role in processes including pre-labor, labor, and post-labor, and neonatal period.…”
Section: Discussionmentioning
confidence: 99%
“…Compassion fatigue scale 'The Compassion Fatigue Scale', which was developed by Pommier (2010) and with which validity and reliability studies were conducted in Turkish by Akdeniz and Deniz 17 , has 24 items and is a 5-point Likert-type scale (1=Never, 2=Rarely, 3=Sometimes, 4=Often, 5=Always). The scale consists of six subscales as kindness (items: 6, 8, 16, 24), indifference (2,12,14,18), common humanity (11,15,17,20), disengagement (3,5,10,22), mindfulness (4,9,13,21), and separation (1,7,19,23). After this calculation, the mean total score was obtained; as the total score increases, the compassion level also increases.…”
Section: Personal Information Formmentioning
confidence: 99%